Production of duodenal ulcers in rats using a combination of gastric secretagogues and their prevention by the gastric antisecretory drug UK-9040 : the natural history, morphology, antral G-cells, plasma gastrin and gastric secretion - Joffe, Stephen Neal (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.D.) -- University of Stellenbosch, 1976.